Saltwater Fish Nanoparticles: Biological Effects on COL1A1 Expression in Fetal Mice and Tablet Formula Optimization - Sandy Christiono; Islamy Rahma Hutami; Suparmi Suparmi; Shaista Afroz; Amara Danish Clarasya; Rayyan Orvin Pradipta Ahmad; Amelia Febriani Subiyono (Jurnal Ilmiah Perikanan dan Kelautan, 2026)
Graphical Abstract  Highlight Research Saltwater fish Nano powder modulates the expression of matrix proteins, influencing early dental tissue development. Administration significantly decreases COL1A1 expression in fetal mouse teeth, affecting biomineralization. Increasing talc concentration improves flowability and formulation stability by reducing angle of repose, Carr’s index, and Hausner ratio. Findings suggest marine-derived nanoparticles regulate cellular differentiation during dental development. Supports potential applications of marine natural materials in prenatal nutrition and dental tissue engineering.   Abstract Saltwater fish nanoparticle-based tablets represent a novel nutritional strategy aimed enhancing dental hard tissue density, particularly enamel. These tablets incorporate bioactive proteins, omega-3 fatty acids, and essential minerals such as calcium, phosphate, and magnesium to support enamel biomineralization. The nanoparticle formulation facilitates efficient cellular absorption, thereby increasing the expression of key enamel proteins like collagen type I alpha 1 chain (COL1A1) during enamel matrix development. This study investigated the effect of saltwater fish nanoparticles on COL1A1 expression in ameloblast cells and evaluated the physicochemical properties of tablets with talc concentrations of 1%, 5%, and 10%. Using a true experimental design with a post-test only control group, two groups of mice were assigned: a control group fed standard diet, and a treatment group fed a standard diet supplemented with saltwater fish nanoparticles (2.17 mg/0.5 mL). Tablet formulations were analyzed across the three talc concentrations. Data were subjected to independent T-tests for COL1A1 expression and One-way ANOVA for physicochemical properties. Results revealed a significant reduction in COL1A1 expression in the treatment group. Additionally, talc concentration significantly influenced tablet physicochemical characteristics, with the 10% talc formulation exhibiting the most optimal properties. These findings suggest potential for nanoparticle-based nutritional interventions to promote enamel formation.